KONTRIBUSI KETEAMPILAN MEMBACA PEMAHAMAN TERHADAP KETERAMPILAN MENULIS TEKS RESENSI SISWA KELAS XI SMK NEGERI 3 PADANG - Oktavia, Afni; Nursaid, Nursaid; Afnita, Afnita; Arma Putri, Delsy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the following. First, to describe the book review writing skills of 11th-grade students at SMK Negeri 3 Padang. Second, to describe the reading comprehension skills of 11th-grade students at SMK Negeri 3 Padang. Third, to analyze the contribution of reading comprehension skills to the review writing skills of 11th-grade students at SMK Negeri 3 Padang. This is a quantitative study using a descriptive-analytical method. This study was conducted on 11th-grade students at SMK Negeri 3 Padang. The data in this study consist of the test scores for reading comprehension of book reviews among 11th-grade students at SMK Negeri 3 Padang and the test scores for writing book reviews among 11th-grade students at SMK Negeri 3 Padang. There are three main findings. First, the reading comprehension skills of 11th-grade students at SMK Negeri 3 Padang are in the “good” category, with a mean score of 79.20. Second, the book review writing skills of the 11th-grade students at SMK Negeri 3 Padang were in the “good” category with a mean score of 85.54. Third, there was a significant positive relationship between reading comprehension skills and book review writing skills with a degree of freedom of n-1 (35-1=32) and a significance level of 95%. H0 is rejected and H1 is accepted because the calculated t-value is greater than the critical t-value, namely 14.06 > 1.697. In other words, the better the reading comprehension skills, the better the students’ ability to write book reviews.